(untitled) (Advances in Civil and Architectural Engineering, 2022)
Participation in social and cultural life is the right of every human being, but for some persons (with disability, chronic illness, mobility and sensory issues…) it is greatly hindered by the inaccessibility of spaces and content. This topic has recently gained importance, owing to our growing awareness of the percentage of persons with mobility problems, and particularly regarding the aging population in many countries. Moreover, for several countries, the issue of accessibility is also related to the growing importance of tourism to their economy or the presence of many persons with disabilities related to wars. This paper presents the research on the evaluation of the accessibility of cultural locations (urban sites, museums, parks, theatres, etc.) through in-depth interviews and surveys with representatives of persons with disabilities, chronic illness, mobility and sensory issue and mental health issues, and by creating an evaluation multicriteria model with guidelines based on these inputs. The results reveal that while it is possible to evaluate the flow and content of cultural activities, there are problems of inaccessibility and lack of awareness among the general and professional public